Dynamic interplay of WRKY, GRAS, and ERF transcription factor families in tomato-endophytic fungal symbiosis: insights from transcriptome and genome-wide analysis - Khan, Ibrahim; Lubna,; Asaf, Sajjad; Jan, Rahmatullah; Bilal, Saqib; Khan, Abdul Latif; Kim, Kyung-Min; Al-Harrasi, Ahmed (Frontiers in Plant Science, 2023)
Plant-microbe interactions play a crucial role in shaping plant growth and development, as well as in mediating plant responses to biotic and abiotic stresses. In this study, we used RNA-seq data to examine the expression profiles of SlWRKY, SlGRAS, and SlERF genes during the symbiotic association of Curvularia lunata SL1 with tomato (Solanum lycopersicum) plants. We also conducted functional annotation analysis by comparative genomics studies of their paralogs and orthologs genes, as well as other approaches, such as gene analysis and protein interaction networks, to identify and characterize the regulatory roles of these TFs in the development of the symbiotic association. We found that more than half of the investigated SlWRKY genes exhibited significant upregulation during symbiotic association, including SlWRKY38, SlWRKY46, SlWRKY19, and SlWRKY51. Several SlGRAS and SlERF genes were upregulated, such as SlGLD2, SlGLD1, SlERF.C.5, ERF16, and SlERF.B12. Conversely, a smaller proportion of SlWRKY, SlGRAS, and SlERF genes were significantly downregulated during symbiotic association. Furthermore, we investigated the possible roles of SlWRKY, SlGRAS, and SlERF genes in hormonal regulation during plant-microbe interactions. We identified several upregulated candidate transcripts likely to be involved in plant hormone signaling pathways. Our findings are consistent with previous studies on these genes, providing further evidence of their involvement in hormonal regulation during plant-microbe interactions. To validate the RNA-seq data accuracy, we performed RT-qPCR analyses of selected SlWRKY, SlGRAS, and SlERF genes, which showed similar expression patterns to those observed in the RNA-seq data. These results confirmed the accuracy of our RNA-seq data and provided additional support for the differential expression of these genes during plant-microbe interactions. Taken together, our study provides new insights into the differential expression profiles of SlWRKY, SlGRAS, and SlERF genes during symbiotic association with C. lunata, as well as their potential roles in hormonal regulation during plant-microbe interactions. These findings could be useful for guiding future research on the ways in which plants and microbes interact, and may ultimately lead to the creation of better approaches for promoting plant growth under stressful conditions.